Factors Associated with Poor Sleep Quality in Postpartum Women: A Crossectional Study - Motta, Ana Júlia Pereira; Lucchese, Roselma; Leão, Graciele Cristina Silva; Rosa, Dayane Eusenia; Gonçalves, Vilmar De Assis, Junior; Mendonça, Revora Silverio (Sleep Science, 2024)
Objective This study aimed to analyze the factors associated with poor sleep quality in women in the postpartum period who were assisted in a municipality in central Brazil.Material and Methods This is a cross-sectional study (n = 400) conducted virtually from 2020 to 2021. Sociodemographic and clinical characteristics, self-perceived sleep, and the Pittsburgh Sleep Quality Index (PSQI) were assessed.Results It was identified that 82% of postpartum women were between 18 and 35-years-old and had an average monthly household income of R$2,339.27 ± 1,812.95. It was also found that 33.50% (95% CI: 28.7–38.0) had sleep disorders (PSQI >10); 70.25% (95%CI 65.8–74.8) had poor sleep quality (PSQI >5); 57.4% (95% CI: 52.0–63.1) had inadequate sleep on weekdays/workdays; and 64.1% (95% CI 59.3–69.2) had unsuitable sleep on weekends/days off. It was found that the factors associated with sleep disturbance were: age between <18 years and >35 years (p = 0.048); difficulty to think clearly (p = 0.043); frequent sadness (p = 0.046); poor sleep quality; low income (p = 0.030); difficulty to think clearly (p = 0.013); and loss of interest in things (p = 0.030). As for sleep on weekdays, the associated factors were: marital status without a partner (p = 0.008); and being a victim of physical violence (p = 0.003). Finally, for sleep on weekends/off: nonwhite skin-color (p = 0.039); and having postpartum depression (p = 0.029).Conclusion The findings of the present study call attention to the impacts of changes in women's bodies, behavior, and interpersonal relationships caused by the arrival of a newborn. We also highlight the need for a multidisciplinary and comprehensive medical approach in this period.
Keywords: postpartum; sleep quality; women's health